ChemInform Abstract: Review of Melt Casting of Dense Ceramics and Glasses by High Gravity Combustion Synthesis. Issue 44 (14th October 2013) - Liu, G. H.; Li, J. T.; Chen, K. X.
Abstract Review: 63 refs.